Distortionary taxation, debt, and the price level - Andreas Schabert; Leopold von Thadden (European Central Bank (ECB), 2006)
This paper considers the nominal and real determinacy of equilibria under an exogenously specified path of interest rates in an economy in which taxation is either lump-sum or distortionary. Under lump-sum taxation, we confirm the well-known finding that equilibria display nominal (in)determinacy if the primary surplus is exogenous (endogenous). Under distortionary taxation, this classification is no longer relevant. Nominal determinacy is always ensured since distortionary taxes establish a link between the allocation and the sequences of taxes and debt and, hence, the price level, regardless of whether the primary surplus is exogenous or endogenous. Distortionary taxation, however, increases the scope for real indeterminacy. As a general feature, the real (in)determinacy of equilibria depends on the interaction of fiscal and monetary policies, i.e. on the sequences of taxes, debt, and interest rates. If, for example, fiscal policy runs a balanced budget the central bank should set the nominal interest rate in a way consistent with long-run deflation in order to ensure real determinacy. This finding is different from a balanced-budget policy under lump-sum taxes where no such qualification with respect to the interest rate needs to be made.
Keywords: E31; E63; 330; distortionary taxes; Monetary and fiscal policy; price level determination; Geldpolitik; Finanzpolitik; Pauschalbesteuerung; Steuerbelastung; Preisniveau; Haushaltskonsolidierung; Theorie